If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(u + -5) = -56 Reorder the terms: -7(-5 + u) = -56 (-5 * -7 + u * -7) = -56 (35 + -7u) = -56 Solving 35 + -7u = -56 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + -7u = -56 + -35 Combine like terms: 35 + -35 = 0 0 + -7u = -56 + -35 -7u = -56 + -35 Combine like terms: -56 + -35 = -91 -7u = -91 Divide each side by '-7'. u = 13 Simplifying u = 13
| 5x+10=8x+4 | | 42+7k=21 | | -3.28=2(1.5y-.5) | | x^2-36=-9 | | y=5x-40 | | (q+1)(2q-3)=3 | | 2x+4=3x-10 | | 9(h-84)-5=77 | | (7y)/(7y+7)+(7y-17)/(6y+6)=(6y+1)/(y+1) | | |36-7|=27 | | o/9+13=-3 | | 0/9+13=-3 | | 2/3v+1/6-7/9-5/6 | | 7y/(7y+7)+(7y-17)/(6y+6)=(6y+1)/(y+1) | | (31/5)y=31 | | 5N(N-1)=N+8 | | 12-9x=17-8x | | 31/5y=31 | | |x-5|+2=9 | | |x-5|-2=9 | | u/2-10=-80 | | 3b^2-b-1=0 | | h/2=-70 | | x+7/x+5 | | 4p^2-4p=0 | | -2.3a+16=-5a-38 | | 10x-27=7x+54 | | (14-y)=12 | | 2x+1=3x-8 | | 8(3x-5)=38 | | 3(6-d)=18 | | 1.2x+3.7=2.2-4.5 |